Information Technology Outsourcing in Nepal: Strengths, Challenges, and Priorities - Paudel, Sushil; Agal, SN; Kumar, Vinish (Nepal Journal of Multidisciplinary Research, 2021)
Nepal has not been able to harness its growth potential on information technology outsourcing on the borders of two of the world's largest outsourcing providers – India and China – due to prolonged political instability. The IT outsourcing industry plays a major role in driving socio-economic growth. The success of IT outsourcing is largely dependent upon the vendor's internal strength, industry-specific environmental factors, and country-specific policies. This research is focused on outsourcing strategies on vendor’s perspective, as many emerging markets continue to struggle to establish a foothold in the international market. A snowball sampling method was used to collect quantitative data among the respondents inside Kathmandu valley and respondents were outsourcing companies, freelancers, consultants, and policymakers. Variables were drawn from the the expert's input and literature review. Data were properly tested for reliability using Cronbach’s Alpha, and results were validated using convergent and discriminant validity. The analysis included descriptive analysis followed by structural equation modelling. The study identified six key strategic factors for emerging market: banking priority to IT outsourcing industry, growth capacity of the service provider, intellectual property, country specific specialization, foreign direct investment, and the HR structure of the vendor. It is suggested that policymakers of emerging nations include IT outsourcing in an economic strategy and prepare baseline framework incorporating these success factors.